Incidence, Risk Factors, and Long-term Outcome of Acute Leukemia Patients With Early Candidemia After Allogeneic Stem Cell Transplantation: A Study by the Acute Leukemia and Infectious Diseases Working Parties of European Society for Blood and Marrow Transplantation. (22nd February 2018) - Cesaro, Simone; Tridello, Gloria; Blijlevens, Nicole; Ljungman, Per; Craddock, Charles; Michallet, Mauricette; Martin, Alexander; Snowden, John A; Mohty, Mohamad; Maertens, Johan; Passweg, Jacob; Petersen, Eefke; et al.
Abstract : The incidence of early candidemia after hematopoietic stem cell transplantation was 1.2%, with a case fatality rate of 22% by day 100. Early candidemia was an independent risk factor for higher nonrelapse mortality and lower overall survival. Abstract: Background: This study was performed to assess the incidence of and risk factors for Candida infection in the first 100 days after allogeneic hematopoietic stem cell transplantation (HSCT) and the impact on long-term survival. Methods: We performed an outcome analysis of 28542 acute leukemia patients who underwent HSCT from 2000 to 2012. There were 347 patients with candidemia by day 100 and 28195 without candidemia or any other type of Candida infection. Results: The incidence of candidemia by day 100 was 1.2% and occurred at a median of 22 days after HSCT. Higher 100-day nonrelapse mortality (NRM; hazards ratio [HR], 3.0, P < .0001) and lower 100-day overall survival (OS; HR, 2.5, P < .0001) were observed in patients with candidemia. The case fatality rate by day 100 in patients with candidemia was 22% (76/347). Factors associated with candidemia occurrence were female gender, bone marrow or cord blood stem cell source, T-cell depletion, use of total body irradiation, and acute graft vs host disease. Among the patients alive at day 100, the 5-year NRM and OS after a median follow-up of 5.6 years (95% confidence interval, 5.5 – 5.7) for patients with and without candidemia were 22.5% vs 13.5%, P < .0001 and 45.6% vs. 53.4%, P = .0003, respectively. In multivariate analysis, the occurrence of a candidemia episode by day 100 was an independent risk factor for higher NRM (HR, 1.7, P = .001) and lower OS (HR, 1.4, P = .001). Conclusions: The early occurrence of candidemia after HSCT is still associated with higher NRM and lower short- and-long-term OS.